Large bite bisphosphite, 2,6-C5H3N{CH2OP(-OC10H6) - Punji, Benudhar; Balakrishna, Maravanji S. (Journal of Organometallic Chemistry, 2007)
<div class="abstract svAbstract " data-etype="ab" style="border: 0px; font-size: 16px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, 'Lucida Sans Unicode', 'Microsoft Sans Serif', 'Segoe UI Symbol', STIXGeneral, 'Cambria Math', 'Arial Unicode MS', sans-serif; color: rgb(46, 46, 46); line-height: 23.68px;"> Large bite bisphosphite ligand, 2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2 (2), is obtained by reacting chlorophosphite, {-OC10H6(μ-S)C10H6O-}PCl (1) with 2,6-pyridinedimethanol in presence of triethylamine.Treatment of 2 with aqueous solution of H2O2 or elemental sulfur resulted in the formation of bis(oxide) or bis(sulfide) derivatives, 2,6-C5H3N{CH2OP(E)(–OC10H6)(μ-S)(C10H6O–)}2 (3, E = O; 4, E = S) in quantitative yield.The 10-membered cationic chelate complex, [RuCl(η6-C10H14)η2-2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2-κP,κP]Cl (5) is produced in the reaction between [Ru(p-cymene)(μ-Cl)(Cl)]2 and bisphosphite 2, whereas the neutral chelate complex, cis-[Rh(CO)Cl{2,6-C5H3N{CH2OP(–OC10H6(μ-S)C10H6O–)}2}-κP,κP] (6) is isolated in the reaction of 2 with 0.5 equiv.of [Rh(CO)2Cl]2.Compound 2 on treatment with M(COD)Cl2 (M = Pd, Pt) produce the chelate complexes, [MCl2{η2-2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2}-κP,κP] (7, M = Pd;10, M = Pt).Similarly the reaction of bisphosphite 2 with Pd(COD)MeCl affords cis-[PdMe(Cl)η2-2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2-κP,κP] (8).Treatment of 2 with [Pd(η3- C3H5)Cl]2 in the presence of AgClO4 furnish the cationic complex, [Pd(η3-C3H5)η2-2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2-κP,κP]ClO4 (9). The binuclear complex, [Au2Cl2{2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2}-κP,κP] (11) is obtained in the reaction of compound 2 with two equiv. of AuCl(SMe2), where the ligand exhibits bridged bidentate mode of coordination. All the complexes are characterized by the 1H NMR, 31P NMR, elemental analysis and mass spectroscopy data. The cationic ruthenium complex 5 is proved to be an active catalyst for the hydrogenation of styrene and α-methyl styrene.

Large-bite bisphosphite, 1,3-C6H4OPOC10H6(μ-S)C10H6O2: synthesis, copper(I), and gold(I) complexes - Balakrishna, Maravanji S.; Kumar, Pawan; Punji, Benudhar; Mague, Joel T. (Journal of Organometallic Chemistry, 2010)
Large-bite bisphosphite ligand 1,3-C6H4{OPOC10H6(μ-S)C10H6O}2 (3), is obtained by reacting chlorophosphonite {OC10H6(μ-S)C10H6O}PCl (2) with resorcinol in the presence of triethylamine. Treatment of 3 with CuCl in 1:1 molar ratio produces a 1D-coordination polymer [CuCl{(–OC10H6(μ-S)C10H6O–)P(–OC6H4O–)P(–OC10H6(μ-S)C10H6O–)}-κP,κP]∞ (4) in good yield. Similar reaction of 3 with two equivalents of AuCl(SMe2) affords a dinuclear complex, [Au2Cl2{(–OC10H6(μ-S)C10H6O–)P(–OC6H4O–)P(–OC10H6(μ-S)C10H6O–)}-κP,κP] (5). Single crystal X-ray structures of the ligand 3 and the complexes 4 and 5 are reported. The gold complex 5 shows dimeric structure supported by strong Au···Au aurophilic interactions.

Ligand-free MnBr2-catalyzed chemo- and stereoselective hydroboration of terminal alkynes - Pawar, Rameshwar B.; Karmur, Mital H.; Punji, Benudhar (Chemistry-an asian jounrnal, 2024)
Developing simple and benign protocols for synthesizing alkenylboronates is crucial as they are synthetically valuable compounds in various organic transformations. In this work, we report a straightforward ligand-free protocol for synthesizing alkenylboronates via atom-economical hydroboration of alkynes with HBpin catalyzed by a manganese salt. The reaction shows a high level of chemo and regioselectivity for the terminal alkynes and exclusively produces E-selective alkenylboronates. The hydroboration scope is vast, with the resilience of a range of synthetically beneficial functionalities, such as halides, ether, alkenyl, silyl and thiophenyl groups. This reaction proceeds through the involvement of a metal-hydride intermediate. The developed alkenylboronate can be smoothly converted to useful C-C, C-N and C-I bond-forming reactions.
Keywords: alkenylboronates; alkyne; Hydroboration; manganese; stereoselectivity